The temperature dependence of amyloid β solubility reveals the hydrophobic effect as the main driving force for fibril formation - Max Lindberg; Jing Hu; Dev Thacker; Emma Sparr; Sara Linse (Proceedings of the National Academy of Sciences, 2026)
The aggregation of amyloid proteins into fibrillar and oligomeric aggregates is linked to a number of neurodegenerative diseases. While the disease onset remains elusive in many cases, an understanding of the driving forces for the aggregation may help finding possible causes. While effects on amyloid formation kinetics are more commonly studied, gaining insights into these driving forces require a thermodynamic approach with equilibrium measurements. Here we investigate the temperature dependence of the solubility of the amyloid beta peptide, A β 42, related to Alzheimer’s disease, using high-performance liquid chromatography coupled to a mass spectrometer and circular dichroism spectroscopy. Samples of 8 to 50 μM A β 42 were incubated for up to 168 h at pH 8.0 and moderate ionic strength at multiple temperatures in the range of 5 to 80 ° C. The remaining monomer concentration was measured after 48 to 168 h, with little change in between suggesting that equilibrium is approached at 168 h. The lowest solubility of 20 ± 10 nM is found around body temperature, with higher solubility at both lower and higher temperatures. This nonmonotonic temperature dependence is indicative of the hydrophobic effect being a major driving force for the fibril formation of this peptide.